Semicircular Canal Pressure Changes During High-intensity Acoustic Stimulation. Issue 7 (August 2017) - Maxwell, Anne K.; Banakis Hartl, Renee M.; Greene, Nathaniel T.; Benichoux, Victor; Mattingly, Jameson K.; Cass, Stephen P.; Tollin, Daniel J.
Abstract : Hypothesis: Acoustic stimulation generates measurable sound pressure levels in the semicircular canals. Background: High-intensity acoustic stimuli can cause hearing loss and balance disruptions. To examine the propagation of acoustic stimuli to the vestibular end-organs, we simultaneously measured fluid pressure in the cochlea and semicircular canals during both air- and bone-conducted sound presentation. Methods: Five full-cephalic human cadaveric heads were prepared bilaterally with a mastoidectomy and extended facial recess. Vestibular pressures were measured within the superior, lateral, and posterior semicircular canals, and referenced to intracochlear pressure within the scala vestibuli with fiber-optic pressure probes. Pressures were measured concurrently with laser Doppler vibrometry measurements of stapes velocity during stimulation with both air- and bone-conduction. Stimuli were pure tones between 100 Hz and 14 kHz presented with custom closed-field loudspeakers for air-conducted sounds and via commercially available bone-anchored device for bone-conducted sounds. Results: Pressures recorded in the superior, lateral, and posterior semicircular canals in response to sound stimulation were equal to or greater in magnitude than those recorded in the scala vestibuli (up to 20 dB higher). The pressure magnitudes varied across canals in a frequency-dependent manner. Conclusion: High sound pressure levels were recorded in the semicircular canals with sound stimulation, suggesting that similar acoustical energy is transmitted to the semicircular canals and the cochlea. Since these intralabyrinthine pressures exceed intracochlear pressure levels, our results suggest that the vestibular end-organs may also be at risk for injury during exposure to high-intensity acoustic stimuli known to cause trauma in the auditory system.